Duration of Type 2 Diabetes Mellitus Over 5 Years, HbA1c Levels Over 7%, Alkaline Phospatase Over 130 IU/L, and C-Reactive Protein Over 3 mg/dL as Risk Factors for Osteoporosis in Type 2 DM Patients - Putra, Gede Mahardika; Kawiyana, Ketut Siki; Wiratnaya, Gede Eka; Suyasa, Ketut (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Type 2 diabetes mellitus (DM) may increases the risk of osteoporosis due to impaired osteoblast and osteoclast function, which affects the morbidity and mortality rates of DM patients. Not many studies investigating the relationship of DM with osteoporosis. AIM: The purpose of this study was to evaluate the duration of DM, hemoglobin A1c (HbA1c), alkaline phosphatase (ALP), and C-reactive protein (CRP) levels as risk factors for osteoporosis. METHODS: Case control study was performed on a total of 44 samples that consist of ostoporosis group and non-osteoporosis group. Difference of HbA1c, ALP, and CRP between groups was evaluated using Chi-square test. RESULTS: Based on statistical analysis, we found that the duration of DM Type II ≥5 years (p = 0.002, odds ratio [OR] 11.08), HbA1c levels ≥7% (p = 0.027, OR 5.4), ALP ≥130 IU/L (p = 0.045, OR 5.2), and CRP ≥3 ng/dL (p = 0.033, OR 4.67) were significant risk factors for osteoporosis. Based on multivariate analysis with logistic regression, we found that risk factors for the duration of DM Type II ≥5 years had the greatest strength of association with osteoporosis. CONCLUSION: In DM patients, duration of DM ≥5 years, HbA1c levels ≥7%, ALP ≥130 IU/L, and CRP ≥3 ng/dL are predictor factors for osteoporosis that can be used in clinical practice. These risk factors can be used as evaluation parameters for DM patients who are suspected to have osteoporosis.